Comparison of the influence of solid and phase change materials as a thermal storage medium on the performance of a solar chimney - Carlos Méndez (88102) (2023)
This paper studies the heat storage system's influence on a solar chimney's power production. This study considers several material types, including solid and phase change materials, at the bottom section of a solar chimney for energy storage, and evaluates their effects on the energy yield and capacity to prolong the power output during the absence of the sun. A computational fluid dynamic model using COMSOL Multiphysics is performed to carry out this work. An initial steady-state analysis using average monthly irradiance is implemented, after which the top two solid and phase change material options are selected. Subsequently, a time-dependent simulation using a typical summer day is carried out for the chosen storage materials. The overall performance results are comparatively assessed in terms of average temperature, power generation, and efficiency. As a result, bismuth-led-tin-cadmium and magnesium chloride hexahydrate present the highest power production among the phase change materials, giving a yearly average power output of 27.46 kW and a storage temperature of about 346 K. On the other hand, sandstone offers the highest overall annual average power production, yielding 31.49 kW, and a storage temperature of 352.17 K. This material also reflects the highest yearly average energy and exergy efficiencies with 0.122% and 0.128%, respectively. Other Information Published in: Energy Science & Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ese3.892